Quercetin Attenuates High-Fat Diet-Induced Excessive Fat Deposition of Spotted Seabass (Lateolabrax maculatus) Through the Regulatory for Mitochondria and Endoplasmic Reticulum - Dong, Yan-Zou; Xia, Tian; Lin, Ji-Bin; Wang, Ling; Song, Kai; Zhang, Chun-Xiao (Frontiers in Marine Science, 2021)
This study aimed to investigate the effects of quercetin (QUE) on fat deposition and the underlying mechanism. Fish were fed four test diets: normal fat diet (NFD), high-fat diet (HFD), and HFD supplemented with 0.5 or 1.0 g/kg quercetin (QUE0.5 or QUE1.0). The results showed that HFD feeding resulted in poor growth and feed utilization while QUE treatment reversed this. The fat contents of serum and liver were increased by HFD and QUE supplementation significantly decreased fat content. Furthermore, gene expressions and ultrastructure observation showed that mitochondrial biogenesis and mitophagy were inhibited and endoplasmic reticulum stress (ERS) in the HFD group. QUE can activate the biogenesis and autophagy of mitochondria and suppress ERS, which is related to its fat-lowering effect.